UZBEK CULTURES AND HOLIDAYS. - Salimova S.S. (Ta'lim innovatsiyasi va integratsiyasi, 2023)
ABSTRACT. This article is about Uzbek cultures and holidays. As you know there are many holidays in Uzbekistan. Culture can be defined as all the ways of life including arts, beliefs and institutions of a population that are passed down from generation to generation. Culture has been called "the way of life for an entire society." As such, it includes codes of manners, dress, language, religion, rituals, art.